Acceptability of Alternatives to Traditional Emergency Care: Patient Characteristics, Alternate Transport Modes, and Alternate Destinations. (2nd October 2015) - Jones, Courtney Marie Cora; Wasserman, Erin B.; Li, Timmy; Shah, Manish N.
Abstract: To determine the acceptability of alternatives to traditional emergency care, we assessed the proportion of subjects willing to consider alternative modes of transportation and alternative destinations. We further identified patient characteristics associated with willingness to consider these alternatives. We conducted a cross-sectional survey study in the emergency department (ED) of an academic medical center. Research assistants screened all non-critically ill ED patients for eligibility and willingness to participate and administered an interview-based survey that included questions on demographic and clinical characteristics, perceived illness severity, and acceptability of alternatives to traditional emergency care for acute illness and injuries. We calculated the proportions and 95% confidence intervals for subjects who found alternative transport modes and destinations acceptable and developed a log-binomial regression model to identify patient characteristics associated with acceptability of alternative modes of transport and alternative destinations. Complete data were available on 1, 058 subjects. Forty-two percent of the study sample arrived to the ED via emergency medical services (EMS). Over two-thirds of the study sample (68.2%) was willing to consider transport via either taxi or medical transport van and 69.0% was willing to consider either transportation to an urgent care center or their primary care physician's office. Other alternatives, including delayed EMS response time, were less frequently endorsed as acceptable alternatives. Subject characteristics associated with willingness to accept alternative modes of transportation included younger age, chief complaint, previous ED use, and place of residence ( p < 0.05). Subject characteristics associated with willingness to accept alternative destinations included younger age, non-white race, lower patient acuity, and lower self-perceived illness severity ( p < 0.05). In our ED, some patients found alternative transport modes and alternative destinations acceptable. We identified patient-level characteristics associated with willingness to accept alternatives; however, the predictive ability and clinical utility of these factors is limited. Future research should further explore the acceptability and effectiveness of these alternative care delivery options.